Development of Local Banana-Based Wine Products Reviewed in Terms of Sugar Content and Dilution - Sudiarta, I Wayan; Ni Luh Putu Putri, Setianingsih; Semariyani, A.A. Made; Dewi, Ni Made Putri Pradnya Paramita; Putri, , Putu Nanda Icaka (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Banana wine has high nutritional content and relatively high antioxidant levels. Thisstudy aims to test and analyze sugar concentration and the effect of optimal dilution toobtain banana wine with good characteristics and by SNI standards. The method used toachieve the objectives is the sugar content in the fermentation media and the amount offermentation media dilution. In this study, several sugar levels were tested (10%, 15%,20%, and 25%) and diluted fermentation media (1:3, 1:4, and 1:5). The data obtainedwere then analyzed using one-way ANOVA. Based on the results of objectiveobservations of the banana wine produced, treatment with 20% sugar content producedthe best banana wine with the characteristics of total sugar 10.66%, alcohol content8.03%, total acid 0.26%, acidity level (pH) 2.37, and total microbes 1.4 x 101 CFU/g,with the highest panelist assessment and typical odor and taste. Subjective researchresults with organoleptic tests showed that the treatment of sugar content and dilutionamount did not change the color and aroma of banana wine. The highest wine tasteassessment was obtained in treating 20% sugar at a dilution of 1:4, which was 5.67(somewhat like it). The highest overall wine acceptance assessment was obtained in thetreatment of 20% sugar at a dilution of 1:4, which was 5.73 (somewhat like it). Themethanol content test results were <0.0036% so in making banana wine from localbananas, it is recommended to use 20% sugar with a dilution of 1:4 fermentation media.Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 3 – Good Health and Well-being|SDG 8 – Decent Work and Economic GrowthSDG 9 – Industry, Innovation and InfrastructureSDG 12 – Responsible Consumption and Production